2020
DOI: 10.3390/cryst10030184
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Zintl‒Klemm Concept for ALn2Ag3Te5-Type Alkaline-Metal (A) Lanthanide (Ln) Silver Tellurides

Abstract: Understanding the bonding nature of solids is decisive, as knowledge of the bonding situation for any given material provides valuable information about its structural preferences and physical properties. Although solid-state tellurides are at the forefront of several fields of research, the electronic structures, particularly their nature of bonding, are typically understood by applying the Zintl-Klemm concept. However, certain tellurides comprise ionic as well as strong (polar) mixed-metal bonds, in obvious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…The corresponding Mulliken and Löwdin charges of YTe, on the other side, clearly point to a small valence-electron transfer unlike that observed for the ionic SrTe, so the Y-Te contacts cannot be depicted as ionic. This outcome is in stark contrast to literature data [59][60][61][62] suggesting ionic rareearth-tellurium interactions, but agrees well with more recent research 23,25,26,28 revealing polar-covalent bonding nature and suggesting the Zintl-Klemm formalism as potentially misleading. Examining the projected COHP of YTe brings to light that the largest bonding contribution originates from Y-4d-Te-5p which changes from bonding to antibonding below the Fermi level.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The corresponding Mulliken and Löwdin charges of YTe, on the other side, clearly point to a small valence-electron transfer unlike that observed for the ionic SrTe, so the Y-Te contacts cannot be depicted as ionic. This outcome is in stark contrast to literature data [59][60][61][62] suggesting ionic rareearth-tellurium interactions, but agrees well with more recent research 23,25,26,28 revealing polar-covalent bonding nature and suggesting the Zintl-Klemm formalism as potentially misleading. Examining the projected COHP of YTe brings to light that the largest bonding contribution originates from Y-4d-Te-5p which changes from bonding to antibonding below the Fermi level.…”
Section: Resultssupporting
confidence: 82%
“…In the cases of the tellurides containing transition-metals, the bonding nature is better described as polar-covalent such that applying the Zintl-Klemm idea to such tellurides could be misleading. [23][24][25][26][27][28] Within the most recent efforts on tellurides comprising posttransition-metals, a new bonding type dubbed 'metavalent' 21,29 or 'hyperbonding' 30 has been proposed. This type of bonding is expected to be at the frontier between entire valence-electron localization as well as delocalization and was introduced based on a portfolio of various quantities, seen both in experiment and calculation.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of the volumes of the unit cells of RbLnZnTe 3 (Ln = Gd, Tb, Dy; Table 1) to those of the isostructural cesium-containing [59] tellurides (V CsGdZnTe 3 = 863.55 Å 3 ; V CsTbZnTe 3 = 857.10 Å 3 ; V CsDyZnTe 3 = 851.11 Å 3 ) shows that the unit cell volumes of the latter are larger than those of the former. This is because of the decreased covalent radius [60] from cesium (2.44 Å) to rubidium (2.20 Å); yet, the unit cell volumes within the series RbLnZnTe 3 (Ln = Gd, Tb, Dy) solely exhibit a very small variation-a circumstance that has also been encountered for different polar intermetallics containing heavier lanthanides [24,[61][62][63]. In the following, the crystal structure of this type of quaternary telluride will be prototypically depicted for RbDyZnTe 3 .…”
Section: Resultsmentioning
confidence: 99%
“…In the spirit of this formalism, the interactions between tellurium atoms and early as well as late TM atoms are frequently described [23][24][25][26] as ionic and covalent, respectively. Yet, more recent research [27][28][29][30] on the electronic structures of certain tellurides, particularly, their nature of bonding, showed that such pictures of the bonding nature should be regarded with concern. Hence, do such Zintl−Klemm treatments help us understanding the nature of bonding in these particular cases, and how else should the bonding nature in such tellurides be described?…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned quantum-chemical examinations [27][28][29][30] of the electronic structures of these tellurides containing (early and) late transition-metals revealed that the TM−tellurium states are well populated such that the majorities of the bonding interactions reside between these states. Since this outcome is indicative of an absence of full valence-electron transfers (like in ionic bonds) from the TM to the tellurium atoms, it was concluded that the TM−tellurium interactions should be depicted as strong (polar) mixed-metal-like bonds rather than ionic bonds.…”
Section: Introductionmentioning
confidence: 99%